Impact of Climate Change in Physical Activity and Competitive Sports: Adaptive Measures and Evaluating Future Impacts in Arunachal Pradesh, India - Sinha, Sandip; Mondal, Tanmoy (Integrated Journal for Research in Arts and Humanities, 2023)
The aim of this paper is to make a detailed study on climate change's impacts on physical activity and organized competitive sports with further attention paid to their adaptation efforts and evaluating the future impacts with special reference to Arunachal Pradesh, India. Linkages between climate and human activity cannot be ignored and it is a universal phenomenon and is certainly possible due to adaptations. These adaptations have direct linkage with physical, mental, emotional, social and overall wellbeing of human beings. Ignoring the degree of adaptation could impact the health upto severe consequences due to climate change. The relationship between sport and environment has to be examined to understand how environment and climatic parameters impacts sport in terms of training, performance and sports injuries. Arunachal Pradesh is a hub of youth potentials especially in sports. Looking at the present climatic crisis, the study aims to assess the impacts of climate change, and measures to be taken by organized competitive sport entities to adapt to the impacts. The study adopts a descriptive analysis including both qualitative and quantitative assessment by exploring secondary information. The findings of the study states that most of the outdoor sport activities especially endurance sports are strongly influenced by meteorological parameters. The effects of weather on sports are varied, performances can get reduced or improved, becomes very severe during extreme weather conditions leading to threat for life. If climate change progresses in scope and severity as predicted, no doubt physical activity and outdoor organized competitive sports is under threat. The valence of this paper lies in its conceptualization of the climate vulnerability on sport activities and its potential to inspire future research and interest in this domain. However, it is important for government, agencies, sports organizations, coaches, athletes, environmentalists, and health experts to have the tools to identify the risks and understand their vulnerabilities.